Comprehension of Ironic Utterances by Bilingual Children - Banasik Natalia; Podsiadło Kornelia (Psychology of Language and Communication, 2016)
This study investigates verbal irony comprehension by 6-year old bilingual children speaking Polish and English and living in the USA. Researchers have predominantly focused on monolingual populations when examining non-literal language in young children. This is the first exploratory study of how irony is comprehended by children growing up in a bilingual setting. Results suggest that 6-year olds from this population score high in decoding the intended meaning behind an ironic utterance and that there is a relation between this ability and the development of their theory of mind (ToM). Interestingly, the data suggests that in the tested sample, no difference could be observed between comprehension of sarcastic irony (i.e., irony containing the element of blame directed towards the addressee) and non-sarcastic irony (irony without criticism towards the interlocutor). The results may be a basis for assuming that irony comprehension may be different in bilingual, compared to monolingual, samples.